A Toolbox for Research – Population Data BC’s tools for overcoming challenges in the data access process - Medearis, Melissa; Mintha, Jim (International Journal of Population Data Science, 2018)
Introduction Navigating the regulatory environment of data access is complex. Where there are common challenges, there are opportunities to develop systems and services that can help researchers. These tools are designed to ensure secure and smooth navigation of the process of data access and data analysis. Objectives and Approach There is increasing focus on technical solutions to support data requests and analysis. We have responded to existing challenges by developing a suite of tools and services including: MetaData Central, DARonline, AppTracker, Snippets, and REDCap. We will describe the obstacles that motivated each tool, how it was built, and how it addresses the original issue. We will also discuss the overall challenges in building these tools, including technical complexity and getting buy-in from data stewards and researchers. Finally, we will touch on some of the progress we have seen based on these tools, and our plans for future development. Results Major obstacles included providing information to researchers to help form their data request, communications among researchers, data stewards and PopData, general automation of procedures, and sharing among researchers. The tools developed in response include: MetaData Central, AppTracker (for project tracking); DARonline (for data requests); REDCap (for primary data collection); and Snippets (for code sharing). MetaData Central has proven to be a valuable resource for all stakeholders to learn basic data descriptions without needing access to the record level data. This helps in making sure the data requested meets the needs of the research project. AppTracker is helpful for monitoring applications, and reduces the time it takes for us to monitor compliance and provide reports. Other tools are newer and have less evaluation information. Conclusion/Implications User-friendly, flexible tools are beneficial for making the data access process smoother and for meeting the evolving needs of researchers and data stewards. These tools can create both transparency through a common source of information and efficiency by automating routine processes.